Konsep Tidur dalam Perspektif Psikologi dan Islam - Mardlatillah, Sandy Diana; Nurjannah (Happiness: Journal of Psychology and Islamic Science, 2023)
Every human being has an obligation to maintain their own health both psychologically and physically. Maintaining health in question covers all sides, both soul, body, mind, and spirit. Allah SWT gave human nature to maintain health from all sides, so that a person is able to fulfill his basic needs first such as eating, drinking, and so on. In Islam, it is highly recommended and pays attention to the lives of its people from the smallest things. The type of research used is qualitative research. The method used in this research is library research, so that most of the literature used to explore data sources comes from library materials and other relevant references such as books and journal articles. The results of this study are based on an Islamic perspective, the concept of sleep is oriented towards Rasulullah SAW, meaning that there are procedures before and after sleeping and the duration of sleep used by Rasulullah SAW is no more than five hours. Meanwhile, from a psychological perspective, there are no procedures applied.